Die geometry induced heterogeneous morphology of polypropylene inside the die during die-drawing process. (April 2019) - Lyu, Dong; Sun, Yingying; Thompson, Glen; Lu, Ying; Caton-Rose, Philip; Lai, Yuqing; Coates, Phil; Men, Yongfeng
Abstract: The morphology distribution of isotactic-polypropylene (iPP) shaped through a die during hot stretching process was investigated via wide-angle X-ray diffraction technique. The evolution of micro-structures in the outer layer (layer closer to the die wall) and the inner layer (layer in the center of die) of die-drawn iPP were both recorded. It turned out that the difference of morphology distribution between outer and inner layers changes with the distance from the die entrance to exit. In general, a larger difference between outer and inner layers could be found at the intermediate deformation region inside the die while such difference disappeared at both of the entrance and exit regions of die. These behaviors could be interpreted as a result of the existence of a heterogeneous distribution of force field inside the die, which was caused by the die geometry and inclination of the drawing force. This work showed that the heterogeneous force field inside the die could be revealed through analyzing the morphology of a die-drawn sample. Graphical abstract: Image 1 Highlights: The heterogeneous force distribution inside the die was revealed by analyzing the polymer morphology instead of simulation. Three deformation regions inside the die are determined by the orientation efficiency along the drawing direction. The difference between inner layer and outer layer inside the die changed with deformation regions. An asynchronous structural development of polymer is found across the transverse direction. Different force distribution was supposed to exist inside the die.